An Analysis of Suggestive Words in Derren Brown and Romy Rafael's Hypnosis - Windy Citra Negara; Dwijani Ratnadewi; Armeria Wijaya (Tell : Teaching of English Language and Literature Journal, 2015)
This research is about an analysis of suggestive words that is used in Derren Brown and Romy Rafael’s hypnosis. This study answers the problems related to the use of suggestive words in hypnosis. These problems are about the type of suggestive words used in hypnosis, the steps to use the suggestive words, the intended meaning of the suggestive words and the reason to use the suggestive words. This research applied descriptive qualitative method. Derren Brown and Romy Rafael used the suggestive words in the form of suggestion to imagine and suggestion to obey. The illocutionary acts proposed by Daniel Vanderveken is used as the main approach in determining the illocutionary acts, beside that Searle’s approach of Speech acts is applied as the supporting theory. The result of the analysis is the suggestive words used by Derren Brown and Romy Rafael were in the form series of words. The series of words presented by Derren Brown and Romy Rafael as a hypnotist can be viewed from different angles depending on the mode of delivery used to change the context. By giving suggestion through a series of words, Derren Brown and Romy Rafael can make people do things that they consider unreasonable as driven by the subconscious mind.